IDENTITIES, CULTURAL MITIGATION AND ETHNIC MINORITY INTERPRETERS - GURUNG, Sangi (Comparative Legilinguistics, 2015)
This paper explores the identity construction of ethnic minority (EM) interpreters in Hong Kong and the way cultural differences are incorporated into interpreting in legal settings. The linkage between the two key themes under this study is intertwined by a proposition that an EM interpreter is able to identify cultural differences at work because of his/her close affiliation with the culture, language and ethnicity. In examining the formation of EM interpreters’ professional identities, the intricate interplay of the interpreters’ perceptions, knowledge, native values and beliefs on the one hand and institutional mechanisms/mainstream practice on the other, will be studied. Based on the theoretical framework of Jenkins’ internal-external dialectic of identification developed in Social Identity (2004) and Rethinking Ethnicity (2008), I will integrate Neuliep’s (2009) contextual approach of intercultural communication to examine the integration of cultural differences in interpreters’ interpretation. The research methods primarily used in this project are Milroy’s (1987, 2003) approach of social networking and critical ethnography (Madison 2005). Social networking has been used as an overarching theme in navigating contacts for collecting data and analysing the network dynamics that influence interpreting practice. Likewise, critical ethnography has been used as a tool to investigate how different power structures impact legal interpreting practice. Need for proper assessment, accreditation, professional development opportunities and the code of ethics have emerged as overlapping topics in the process of data collection. As interpreting practice in EM languages in Hong Kong is still relatively unexplored, the project aims at providing viable recommendations to the development of the interpreting profession in legal settings, in particular in Hong Kong.